Health and nutritional status of children enrolled with a charitable trust school in rural service area of a medical college in coastal Karnataka - Farooq, Umer; K. M., Akshaya (International Journal Of Community Medicine And Public Health, 2018)
Background: Healthy children are the base for a healthy nation. Children are quite vulnerable at this growing age and hence are prone to fall victim to many diseases, thus affecting their normal growth and development. School health program was started as a total health care delivery system in our country with a purpose of addressing the health needs of children. This study was carried out in a selected school of rural Mangaluru, Karnataka to assess the health and nutritional status of the children. Methods: A cross-sectional study was conducted during July and August 2017 among all the school children of a charitable school in a rural area of coastal Karnataka. Data regarding anthropometric measurements, refractory error, medical problems and minor ailments were collected using a predesigned health card. Data was entered in Microsoft excel spreadsheet and analysed using SPSS version 23. Results: A total of 773 children were examined. Dental caries was the most common illness found in 29.6% of children followed by refractive errors in 10.7% of the children. About 13% were underweight and 2% were overweight for age. Conclusions: The most common morbidities found were dental caries, pallor, refractory error and anaemia. Overweight was also seen in the children and needs to be addressed. A well implemented school health programme has the potential to provide comprehensive preventive and curative health services to school children.